"El Cotidiano del Cuidador de Niños con Síndrome de Down en Etapa Pre-Escolar" - Leyva Vargas, Mayra Julissa (2016)
In the present research of qualitative nature seeks to identify the everyday caregivers caring for children with Down syndrome, seeks to discover and understand the essence of the phenomenon of everyday life, why four caregivers with children he met syndrome Down in school age from school for special children "Angel of God" Chepén. The methodological path that was used was phenomenological and the findings show that a child with Down Syndrome by its very nature constantly need the care and attention of caregivers, this is clearly evident in their everyday since we got incidents that caregivers every day get up early to attend their children, putting their best efforts, dedication and ready to fight to get ahead; perform different care with your child in addition to therapies and daily exercises are an important part of everyday also assume that for most caregivers have with them a child with Down syndrome means a great blessing in their lives. KEYWORDS: Everyday. Caregiver. I care. Children (as) with Down syndrome.